Quality of dying and death desired by residents of Kagawa Prefecture, Japan: a qualitative study - Kanae Kanda; Nobuko Takashima; Yoshimi Tsuji; Katsunori Yokoyama; Tomohiro Hirao (Komiyama Printing Co. Ltd, 2019)
Abstract Background Achieving a desirable death is an urgent aging-related problem in Japan. However, measures of the quality of death and dying in Japan are lacking. This study aimed to identify components of a desirable death in the residents of Kagawa prefecture, Japan, through focus group interviews. Methods A group interview was conducted with 30 residents aged 20-80 (M age = 50.9, SD = 22.1 years; 43.3% ≥ 65 years; 40.0% unemployed) who had experienced the death of a closely associated person. Participants were grouped into four generations with diverse characteristics (e.g., age, sex, occupation). The interview lasted 1-2 h and involved one interviewer, one observer, and one recorder. The interview theme was "What is a desirable death?" Participants were asked "What do you want to achieve before you die?" or "What would a close friend want to experience when death is near?" We then extracted important items related to "desirable death" using serialization and observation records, while also consulting three analysts. The analysis results of the four generations were ultimately integrated into final categories. Results The most common experience of a familiar death was that of parents, followed by grandparents. Half of participants had witnessed the death. Through category analysis, eight important categories related to desirable death were ultimately extracted. Nine items were identified as common to all generations. While the elderly generation had wide-ranging opinions, the younger generations' opinions tended to concentrate on satisfaction with life and family relations. Conclusion Eight concepts were extracted as important factors of a desirable death from the residents of Kagawa prefecture, Japan.